THE PSEUDO HAPPINESS AS SONG STRATEGY’S SIMULACRA VERSUS PANOPTIC: BTS’S SONGS AND BTS MEMBERS - Angeliqa, Fitria; Andriani, Fizzy (WILAYAH: The International Journal of East Asian Studies, 2024)
The reflections of joy in the lyrics are part of the singer’s message tactic in his songs. Even so, with the overall packaging of the singer’s appearance. The problem is when world-class singers sing self-motivating songs for their listeners, at the same time, life’s troubles become familiar to the singer. Many articles also reported how severe depression, mental health, and suicide occurred in the lives of these artists. Demi Lovato, Shia, and Ariana Grande are some Western artists claiming to have experienced mental health problems. In the ranks of Korean artists, names such as Twice Jeongyeon, AOA Kwon Mina, HyunA, Red Velvet Wendy, and Super Junior Heechul are artists who have also experienced mental health problems and severe depression. The same thing happened to the BTS members. RM and Suga are two members who have admitted to experiencing depression and seeing life as an uphill struggle. This study aims to describe how BTS songs with the theme ’Love yourself’ do not reflect the lives of BTS members under strict agency rules and fans’ supervision. Ultimately, the theme of ’love yourself’ is just a simulation strategy that generates ’false joy’ for the members but has a substantial economic impact on the agency. This study uses the concepts of simulacra, panopticon, and duality reflection. At the same time, the research method is qualitative, with document study as a data collection technique. The unit of analysis is the text, namely the BTS song lyrics with the theme ’love yourself’ and media reports about the members’ lives. These two data are then compared and produce a simulacra picture because there is no reflection on what is being sung and what the members are experiencing. A life full of surveillance from fans and companies removes the privacy boundaries of the members who are – in the end – just a commodity for business turnover. It is where the irony occurs. The pseudo happiness experienced by these members generated many economic benefits for the agency. Increasing the number of listeners, purchasing merchandise, selling concert tickets, traffic on social media, and brand endorsements are essential aspects that can be monetized by the agency, which accompanies the fame of the songs sung by BTS. While living without romantic relationships, solitude, and loneliness, the prohibition of direct interaction via social media with fans are some things that fence off the members’ lives and make them even more alienated from social life.